Antimalarial, Antioxidant Activities and Chemoprofile of Sansevieria liberica Gerome and Labroy (Agavaceae) Leaf Extract - Ifeoma Celestina Orabueze; Sarah Chiamaka Uzor; Bou Ndiaye; Desire Uba; Duncan Azubuike. Ota; Joseph Agbedahusi (Hindawi Limited, 2021)
Background. Sansevieria liberica Gerome and Labroy (Agavaceae) is a religious and ornamental perennial plant with highly valued medicinal usage in Nigeria. Sansevieria liberica is used in the management of malarial fever. The ease of development of resistance to available antimalarial drugs has resulted in increased clinical failure and mortality. The study investigated the antimalarial effects of Sansevieria liberica (SL) leaf extract in mice infected with Plasmodium berghei. Materials and Methods. The ability of SL leaf extract to suppress the growth of malaria parasites in early (suppressive) and established (curative) infections was established using animal models. The mean survival time (MST) was determined. The antioxidant potential was established using two standard in vitro models. High-performance liquid chromatography (HPLC) and phytochemical analysis methods were used to create a chemoprofile fingerprint of SL hydroethanolic leaf extract. Results. At 200, 400, and 400·mg kg−1, SL produced 68.71, 70.74, and 75.09% parasite suppression in the suppressive model while the curative model gave a percentage of cure of 71.09, 72.60, and 62.09, respectively. The animals lived longer compared to both negative and positive controls but were not fully protected. The IC50 values of SL and vitamin C were calculated to be 3.599 µg mL−1 and 3.08 µg mL−1, respectively. The reducing power of vitamin C was significantly (P<0.05) higher than that of SL extract. Some flavonoids were established as possible marker compounds for SL leaf extract. Discussion and Conclusions. The antimalarial assay results demonstrated that the use of SL in folk medicine may have scientific support.